2017
DOI: 10.1177/0284185117740759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of contrast-enhancement on diffusion weighted imaging and apparent diffusion coefficient measurements in 3-T magnetic resonance imaging of breast lesions

Abstract: Background The effect of gadolinium-based contrast agents on diffusion-weighted imaging (DWI) measurements of breast lesions is still not clear. Purpose To investigate gadolinium effects on DWI and apparent diffusion coefficient (ADC) in breast lesions and normal parenchyma with 3 Tesla contrast-enhanced MRI. Material and Methods Pre- and post-contrast DWI (b = 0 and b = 1000 s/mm) were acquired in 47 patients. Measured ADC values, pre- and post-contrast T2 signal intensity (T2 SI) and contrast-to-noise ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
5
2
1
Order By: Relevance
“…However, AUCs were almost identical (precontrast 0.965; postcontrast: 0.968). Moreover, Cipolla et al 18 reported a significant difference (−34%, P < 0.01) after GBCA administration, but in this study, the GBCA amount was relatively high (0.2 mmol/kg), like in Arponen et al 15 At 1.5 T, a higher absolute difference in ADC mean was found in malignant lesions at postcontrast, compared with 3.0 T, although both results were nonsignificant. Studies that analyzed the ADC mean at 1.5 T found various differences in effect.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…However, AUCs were almost identical (precontrast 0.965; postcontrast: 0.968). Moreover, Cipolla et al 18 reported a significant difference (−34%, P < 0.01) after GBCA administration, but in this study, the GBCA amount was relatively high (0.2 mmol/kg), like in Arponen et al 15 At 1.5 T, a higher absolute difference in ADC mean was found in malignant lesions at postcontrast, compared with 3.0 T, although both results were nonsignificant. Studies that analyzed the ADC mean at 1.5 T found various differences in effect.…”
Section: Discussioncontrasting
confidence: 52%
“…13 Prior studies on the effect of contrast agent on ADC measurements are small in sample size up to 62 patients. [14][15][16][17][18][19] Only in a publication using DWI with additional background body suppression, around 150 patients were analyzed. 20 Moreover, postcontrast DWI is evaluated up to 10 minutes after contrast administration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MR diffusion-weighted imaging (DWI) is an MRI functional imaging that non-invasively detects the diffusion movement of water molecules within living tissues, and the automatically generated apparent diffusion coefficient (ADC) contains abundant texture information to quantitatively detect the extent of restricted diffusion of water molecules (5). Previous studies mostly used the method of delineating a single-slice region of interest (ROI) to obtain the mean ADC value to quantify the restricted diffusion of water molecules at the lesion site (6,7). However, the mean ADC value cannot comprehensively reflect the overall ADC information of the lesion, and it ignored the heterogeneity within benign and malignant lesions (8).…”
Section: Introductionmentioning
confidence: 99%
“…Ωστόσο, οι Cipolla και συν. συμπέραναν ότι υπήρχε στατιστικά σημαντική διαφορά μόνο στις κακοήθειες[178]. Το αποτέλεσμα της επίδρασης του σκιαγραφικού στην τιμή του ADC δεν περιορίζεται μόνο στο μαστό.…”
unclassified